Evaluation of the relationship between central serous chorioretinopathy and liver cirrhosis: A nationwide, population-based study. Issue 6 (2nd June 2021) - Hsu, Chia-Chen; Chen, Yi-Hao; Huang, Ke-Hao; Chen, JiannTorng; Chung, Chi-Hsiang; Liang, Chang-Min; Chien, Wu-Chien; Chen, Ching-Long
Abstract : Background: Central serous chorioretinopathy (CSCR) and liver cirrhosis share numerous risk factors and may have possible connections. We aimed to investigate whether patients with liver cirrhosis and the severity of cirrhosis have an increased incidence of CSCR. Methods: This population-based retrospective cohort study was conducted by collecting data from the Taiwan National Health Insurance Research Database from January 1, 2000, to December 31, 2015. We included patients who were newly diagnosed with cirrhosis and selected an equal number of sex- and age-matched control subjects. The effect of cirrhosis on the risk of CSCR was examined via a Cox proportional hazard regression analysis. The cumulative incidence of CSCR was assessed with the Kaplan-Meier method and the log-rank test. Results: Both groups in this study comprised a total of 25 925 individuals. The cirrhotic patients had a significantly higher cumulative risk of developing CSCR in following years than patients without cirrhosis (log-rank test < 0.001). Furthermore, compared with noncirrhotic patients, the risk of CSCR was increased 3.59-fold (95% confidence interval [CI], 2.31-5.28) in cirrhotic patients with complications, and 2.34-fold (95% CI, 1.27-3.24) in cirrhotic patients without complications. Additionally, male sex, springtime, diabetes mellitus, hepatitis B virus, and hepatitis C virus statistical significantly increased the incidence of CSCR. Conclusion: Cirrhosis is an independent indicator of CSCR. Among the cirrhotic population, patients with ascites and other complications have a higher incidence of CSCR than those with uncomplicated cirrhosis. Physicians should be observant when managing cirrhotic patients with visual disturbances.